White reading Giambattista Vico: the false in the true and the ironic conditions of historiographic liberty - Maria-Benedita Basto (Práticas da História, 2018)
This article deals with Hayden White’s chapter on Giambattista Vico’s tropological model of historical transformation, which is part of his seminal collection of essays Tropics of Discourse. Focussing on White’s understanding of how Vico could inspire a critical history of historiographic consciousness, it is demonstrated how his reading of Vico’s poetics of irony opens up a creative tension between discourse and the world, which can serve as a theoretical framework for liberty and critique in historiography.